A fluidic circuit based, high-efficiency and large-scale single cell trap. Issue 23 (17th October 2016) - Mi, Lu; Huang, Liang; Li, Junxiang; Xu, Guoqiang; Wu, Qiong; Wang, Wenhui
Abstract : Equivalent resistive electric circuit inspired, deterministic single cell trap with high efficiency and flexibility for large scale cell patterning. Abstract : Single cell traps have important applications in biological cell manipulation and analysis. This paper describes a novel single cell trap design and device with a matrix of cell trap units inspired by an equivalent resistive electric circuit. This fluidic device follows the least flow resistance path principle of such devices allowing deterministic single cell trapping with high efficiency and flexibility for large scale cell patterning.